Dashboard Manajemen Donor Darah dengan Admin Panel dan Monitoring Stok Berbasis Web - Meike Mandome (LPPM Universitas Ibnu Sina Batam, 2026)
The Blood Transfusion Unit (UTD) faces challenges in managing donor data and blood stocks, which are not yet fully computerized, making it vulnerable to recording errors and information delays. This study aims to design and implement a Blood Donor Management Dashboard with a Web-Based Admin Panel and Stock Monitoring to address these challenges. The system design was conducted using the waterfall method, which includes communication, planning, modeling, construction, and implementation. Functional requirements were obtained through literature studies, interviews with UTD officers, and direct observation of the donor data collection and blood stock recording processes. The system modeling is presented in use case diagrams, activity diagrams, sequence diagrams, and class diagrams. While the system construction uses the CodeIgniter framework with a MySQL database. The results of the study are a dashboard design and prototype that provides two levels of access rights, namely admin and donor, with features for verified donor registration, donor search, blood requests, and blood stock monitoring. The resulting design has the potential to support traceability of donor data and transparency of blood availability information. Empirical system testing and measuring its impact on UTD service performance are future research agendas.